Study on Modified Hummers Method for Partially Oxidized Graphene Oxide Synthesis - Lim, Wan Sin; Chong, Kwok Feng (Trans Tech Publications, Switzerland, 2020)
Graphene oxide (GO) is a promising material that currently a common precursor in the synthesis of graphene material. GO has emerged as a rapidly developed material due to its remarkable application in electronics, energy storage, biomedical and chemistry. However, controlling the oxygen content in the GO is one of the significant factors for tailoring GO that able to fulfil various applications. In this paper, diluted sulfuric acid was employed during the oxidation. Based on the characterization results from Fourier Transform Infrared Spectrometer (FTIR), Ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA) it found that the partially oxidized graphene oxide (PGO) was fabricated. The PGO synthesis show an insignificant absorption of C=O peak in FTIR and weak peak intensity at 300 nm for UV-Vis analysis that found in fully oxidized graphene oxide. Therefore, the PGO synthesis claimed to be partially oxidized.